ANALISIS NILAI MORAL PADA LIMA CERPEN KARYA KUNTOWIJOYO DALAM BUKU DILARANG MENCINTAI BUNGA-BUNGA - Wasi'ah, Dede; Saripah, Tuti; Stiyanti, Dela Wahyu; Mustika, Raden Ika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study aims to analyze the moral values contained in five short stories by Kuntowijoyo in a collection of short stories recorded in a book titled "Forbidden to love the flowers". This research is descriptive qualitative research that is data collecting technique by utilizing library study so that it can describe intactly moral value contained in five short stories by Kuntowijoyo. The results of this research have been done is to know the moral values in each Kuntowijoyo short story and researchers analyzed five short stories, namely: 1) short stories are forbidden to love the flowers contain moral values about a serenity, tranquility and peace of soul; 2) a dog's short story contains a moral value about the importance of a tolerance; 3) a short piece of wood for God contains a moral value of sincerity and intent; 4) fish shorts in jar containing the moral value of reexamining the beliefs of a society; 5) short stories fishing fish in the river contains moral values to be wise again to respond between the desires and feelings of others.